2015
DOI: 10.1111/dom.12515
|View full text |Cite
|
Sign up to set email alerts
|

Sleep efficiency as a determinant of insulin sensitivity in overweight and obese adolescents

Abstract: Insulin resistance (IR) occurs in a transient manner during puberty. Obese adolescents may be at risk for persistent IR during puberty. The objective of the study is to review the literature on the association of the anthropometry and lifestyle characteristics with insulin sensitivity in overweight and obese adolescents, and include data from a new study. Relevant papers were selected and reviewed. In addition, 137 overweight and obese adolescents (42 male/95 female, age 14.4 ± 2.3 years, BMI z-score +3.3 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 71 publications
(155 reference statements)
1
30
1
Order By: Relevance
“…Lower sleep efficiency (the percentage of time in bed that is spent asleep) also predisposes to IR in overweight and obese adolescents 121. In one study, more variability in sleep duration was associated with higher insulin levels 101.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower sleep efficiency (the percentage of time in bed that is spent asleep) also predisposes to IR in overweight and obese adolescents 121. In one study, more variability in sleep duration was associated with higher insulin levels 101.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 99%
“…Although there are considerably less available data in children examining these associations than in adults, several studies have shown that insufficient sleep is associated with IR in obese children (but not in normal-weight children) and normal-weight and obese adolescents independently of obesity 118121. Lower sleep efficiency (the percentage of time in bed that is spent asleep) also predisposes to IR in overweight and obese adolescents 121.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 99%
“…Studies have found that poor SE is associated with obesity, metabolic syndrome, and hypertension . Besides, SE was also found to be a significant contributor for the insulin sensitivity in overweight and obese adolescents . However, there is no evidence on the association between SE and DM based on PSG records.…”
Section: Introductionmentioning
confidence: 99%
“…SE, which is usually the measure used to evaluate individuals for sleep fragmentation, is defined as the ratio of time spent asleep to total time in bed multiplied by 100 . Studies have found that poor SE is associated with obesity, metabolic syndrome, and hypertension . Besides, SE was also found to be a significant contributor for the insulin sensitivity in overweight and obese adolescents .…”
Section: Introductionmentioning
confidence: 99%
“…As expected, pubertal children with morbid obesity had a significantly higher HOMA‐IR than prepubertal children or children who were overweight. High HOMA‐IR in children with morbid obesity in this and previous studies indicates that these children in particular are at high risk of β‐cell exhaustion, which can result in decreased and insufficient β‐cell secretion and T2DM . The PREVIEW study aimed to provide more insight into longitudinal IR development during puberty in a 2‐year follow‐up design.…”
Section: Discussionmentioning
confidence: 99%